STUDENTSâ ACHIEVEMENT IN READING COMPREHENSION USING COOPERATIVE LEARNING TYPE JIGSAW AT THE ELEVENTH GRADE STUDENTS OF MA NIPI RAKHA AMUNTAI - Annisa, Rafika (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2018)
Reading is taught in Indonesian schools to enable the students to read and understand a text and any material written in English. Unfortunately, students still have difficulties to master reading skills. The eleventh grade of MA NIPI RAKHA Amuntai in 2015/2016 are the classes that had this problem. Then, to solve the problem, the Jigsaw Method is used in order to improve studentsâ reading comprehension achievement. The aim of this study is to find out whether there is any improvement in studentsâ reading comprehension achievement of students who are taught by using the Jigsaw Method. This study uses quasi-experimental design. The finding of the research shows that there are improvements in the two classes. The average score of pre-test and post-test of an experimental class are 74.55 and 84.24, while control class only gets 69.99 in pre-test and 72.18 in post-test. In addition, the calculation of t-test result is 2.06 is higher than the t-table 1.67. Based on research finding, Jigsaw Method is suggested to be used as one of the methods in teaching reading comprehension, and this study is also suggested for other researchers who want to conduct similar area on the use of Jigsaw method.